Low prevalence of HIV in the northern Cameroon: contribution of some AIDS restriction genes and potential implications for gene therapy - Djataou, Patrice; Djuidje Ngounoue, Marceline; Nkenfou-Tchinda, Carine Nguefeu; Ngoufack, Marie Nicole; Elong, Elise; Tiga, Aline; Muluh, Clifford; Kadji Kameni, Joelle; Djaouda, Moussa; Ndjolo, Alexis; Nkenfou, Celine Nguefeu (Frontiers in Genetics, 2024)
Background: HIV infection and its progression to AIDS depend on several factors including host genetic factors. The immunological mechanisms of host resistance to HIV infection greatly influence the prevalence of HIV in a given region. Worldwide, Cameroon not exempted, the frequency of AIDS-associated genes varies and may influence this prevalence. The North and Far North Regions of Cameroon have had the lowest HIV prevalence in the country for many years despite risky behaviors associated with their customs and habits. In this work, we seek to explore the contribution of host genes to the HIV low prevalence in these regions.Methodology: Five genes variants previously described as HIV AIDS related were studied.These genes are: CCR5Δ32, CCR5promoter59029G, CCR2-64I, SDF1-3ʹA and Trim5α(R136Q). A total of 384 consented participants were included in this study. The HIV serological status was confirmed using national algorithm. Genomic DNA was extracted from the buffy coats and used for genotyping. The results obtained were compiled in Excel 2016, Epi Info 7.1 and snpStats software and Chi 2 tests allowed us to compare the frequencies of the AIDS related alleles in the North with those in other Regions of Cameroon and to measure the impact of these ARGs on protection against HIV.The frequency of protective alleles CCR5Δ32, CCR5promoter59029G, CCR2-64I, SDF1-3ʹA and Trim5α(R136Q) was 0.005; 0.533; 0.462; 0.542 and 0.785 respectively. These allelic frequencies exhibited a significant difference when compared to those obtained in other regions of Cameroon (P < 0.01). Protective alleles were predominant in the Northern region compared to others and were associated with resistance to HIV [(P<0.0001); OR=2.02 CI, 95%(1,31-2,72)].The higher frequency of HIV-protective alleles in the northern regions may be a contributing factor to the lower prevalence of HIV. Nevertheless, this should be reinforced by other preventive and surveillance methods to guarantee the sustained low prevalence. HIV can develop resistance through the process of mutation, but the host targets themselves are genetically stable. The study of these host genetic restriction factors is of great value in the design of a practical cure for HIV infection or an effective vaccine.